Tom Swift and His Electric Locomotive; Or, Two Miles a Minute on the Rails - Appleton, Victor (Salt Lake City, UT : Project Gutenberg, 1998)
"Tom Swift and His Electric Locomotive; Or, Two Miles a Minute on the Rails" by Victor Appleton is a novel published as Volume 25 in the original Tom Swift series. When railroad president Richard Bartholomew faces bankruptcy, he contracts Tom Swift to build a revolutionary electric locomotive capable of reaching 120 miles per hour. But the ruthless owner of a competing railroad will stop at nothing to sabotage the project. Tom and his friends face hired thugs and life-threatening attacks as they race to complete the massive Hercules 0001 locomotive. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Tom_Swift_and_His_Electric_Locomotive
Release date is 1998-06-01
Produced by Anthony Matonac
Keywords: Adventure and adventurers -- Juvenile fiction; Swift, Tom (Fictitious character) -- Juvenile fiction; Electric railroads -- Juvenile fiction